Waste as a factor of environmental pollution, peculiarities of its management - Soya, Vladyslav; Korniienko, Iryna; Yastremska, Larysa; Anatskyi, Andrii; Kovalenko, Alla; Filimonenko, Olha; Korniienko, Yurii (Problems of Environmental Biotechnology, 2024)
The features of waste management are considered